Enhancing students' conceptual understanding of biodiversity through gamification-based learning using powerpoint media (FaunaPlay) - Pradesti, Rahmadiva; Komala, Ratna; Isfaeni, Hanum (Universitas Negeri Jakarta, 2025)
Conceptual understanding in biology is crucial for addressing global and complex issues. However, students often struggle to grasp biological concepts, thus requiring the support of interactive and engaging learning media. This study aims to develop and evaluate a gamification-based learning approach using PowerPoint media to enhance conceptual understanding of biodiversity, specifically the Felidae family. The research method used in this study is Educational Design Research (EDR) with the Hannafin and Peck (1988) model. Hannafin and Peck model is structured around three distinct phases i.e. needs assessment, design, and development/implementation. Each phase includes evaluation and revision. Data analysis includes assumption tests such as normality and homogeneity tests, as well as effectiveness tests including paired sample T-tests and normalized gain analysis. The subjects of this research are 10th-grade students and Biology teachers at SMAN X Jakarta Timur. The gamification-based PowerPoint learning media (FaunaPlay) is highly feasible to be used as a learning tool and is effective in enhancing the conceptual understanding of 10th grade high school students on the topic of biodiversity, specifically the Felidae family. This study recommends implementing the gamification-based learning media (FaunaPlay) in classroom instruction to enhance conceptual understanding of biodiversity (Felidae). The media can be utilized by teachers as a practical tool during teaching and learning activities. Furthermore, it provides a valuable reference for researchers to develop similar gamified learning media aimed at improving educational quality.